Exploring formation scenarios for the exomoon candidate Kepler 1625b I - Moraes, R. A. [UNESP]; Vieira Neto, E. [UNESP] (Oxford Univ Press, 2020)
If confirmed, the Neptune-size exomoon candidate in the Kepler 1625 system will be the first natural satellite outside our Solar system. Its characteristics arc nothing alike we know for a satellite. Kepler 1625b I is expected to be as massive as Neptune and to orbit at 40 planetary radii around a ten Jupiter mass planet. Because of its mass and wide orbit, this satellite was first thought to be captured instead of formed in situ. In this work, we investigated the possibility of an in situ formation of this exomoon candidate. To do so, we performed N-body simulations to reproduce the late phases of satellite formation and use a massive circumplanetary disc to explain the mass of this satellite. Our setups started soon after the gaseous nebula dissipation, when the satellite embryos are already formed. Also for selected exomoon systems, we take into account a post-formation tidal evolution. We found that in situ formation is viable to explain the origin of Kepler 1625b I, even when different values for the star-planet separation are considered. We show that for different star-planet separations the minimum amount of solids needed in the circumplanetary disc to form such a satellite varies, the wider is this separation more material is needed. In our simulations of satellite formation, many satellites were formed close to the planet, this scenario changed after the tidal evolution of the systems. We concluded that if the Kepler1625 b satellite system was formed in situ, tidal evolution was an important mechanism to sculpt its final architecture.
Keywords: planets and satellites: formation; planets and satellites: individual (Kepler 1625b I)